Epidemic patterns of the different influenza virus types and subtypes/lineages for 10 years in Chongqing, China, 2010-2019 - Xiaoqing Fu; Jiang Long; Yu Xiong; Zhifeng Li; Jule Yang; Dechao Tian; Zhourong Li; Shuang Yang; Li Qi (Taylor & Francis Group, 2024)
To optimize seasonal influenza control and prevention programs in regions with potentially complicated seasonal patterns. Descriptive epidemiology was used to analyze the etiology of influenza, and chi-square tests were used to compare the epidemic patterns among different influenza virus types and subtypes/lineages. From January 2010 to December 2019, a total of 63,626 ILI cases were reported in Chongqing and 14,136 (22.22%) were laboratory-confirmed influenza cases. The proportions of specimens positive for influenza A and influenza B were 13.32% (8,478/63,626) and 8.86% (5,639/63,626), respectively. The proportion of positive specimens for influenza A reached the highest in winter (23.33%), while the proportion of positive specimens for influenza B reached the highest in spring (11.88%). Children aged 5-14 years old had the highest proportion of positive specimens for influenza. The influenza virus types/subtypes positive was significantly different by seasons and age groups (P<.001), but not by gender (p = .436). The vaccine strains were matched to the circulating influenza virus strains in all other years except for 2018 (vaccine strain was B/Colorado/06/2017; circulating strain was B/Yamagata). The study showed significant variations in epidemic patterns, including seasonal epidemic period and age distributions, among different influenza types, subtypes/lineages in Chongqing. Influenza vaccines matched to the circulating influenza virus strain in nine of the ten years. To prevent and mitigate the influenza outbreaks in this area, high risk population, especially children aged 5-14 years, are encouraged to get vaccinated against influenza before the epidemic seasons.